The Pigeon finds a hot dog! - Willems, Mo. (New York : Hyperion Books for Children, 2004)
Pigeon learns about sharing when a curious duckling keeps asking questions about the hot dog Pigeon has found.
Ages 2-6.
A Junior Library Guild selection.
Keywords: Pigeons -- Fiction; Ducks -- Fiction; Sharing -- Fiction; Pigeons -- Juvenile fiction; Ducks -- Juvenile fiction; Sharing -- Juvenile fiction